2019
DOI: 10.1051/smdo/2019001
|View full text |Cite
|
Sign up to set email alerts
|

An example of design, optimization, stabilization and noise performances of resonator-based optoelectronic oscillators

Abstract: In this paper we talk about oscillators of optoelectronic type with intensity modulators and high-quality optical resonators technology. This subject is illustrated by an example of realization from the material to the characterization of the realized oscillator. It is explained how such an oscillator is designed and how it can be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Sound absorption of multilayer configuration of hybrid foam analyzed numerically using COMSOL Multiphysics [7][8][9]. In component section, using the geometry option, a block created and the plane partitioned into 5 domains with the help of Boolean operation.…”
Section: Numerical Simulation 261 Multilayer Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sound absorption of multilayer configuration of hybrid foam analyzed numerically using COMSOL Multiphysics [7][8][9]. In component section, using the geometry option, a block created and the plane partitioned into 5 domains with the help of Boolean operation.…”
Section: Numerical Simulation 261 Multilayer Simulationmentioning
confidence: 99%
“…Adaptive algorithms are used to detect the radiating source which is not familiar with weighted classical array of sensors [7]. The study reported that the material characterization is used to design resonator by optimization process [8]. Also, that the non-acoustic parameter needed for numerical simulation can be predicted using inverse characterisation with different algorithm for instance particle swarm optimization algorithm (PSO) [9], genetic algorithm [10] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Every researcher and engineer who works on oscillators knows that it is essential to meet the Barkhausen criteria before being able to start an oscillator. An example is given through these references corresponding to work on crystal oscillators and other types of optoelectronic oscillators [2][3][4][5][6]. This does not guarantee that the oscillator will be stable and that the oscillation will continue, but it is an essential part.…”
Section: Heinrich Barkhausen's Main Contributions To Oscillatorsmentioning
confidence: 99%